2005
DOI: 10.1128/mcb.25.13.5607-5615.2005
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Mice Lacking the Zinc Uptake Transporter ZIP3

Abstract: The mouse ZIP3 (SLC39A3) gene encodes an eight-transmembrane-domain protein that has been conserved in mammals and can function to transport zinc. To analyze the expression of ZIP3 in the early embryo and neonate and to determine its in vivo function, we generated ZIP3 null mice in which the ZIP3 open reading frame was replaced with that of the enhanced green fluorescent protein (EGFP) reporter. EGFP fluorescence revealed that ZIP3 was expressed in the inner cell mass of the blastocyst and later during embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 46 publications
(64 reference statements)
4
77
0
Order By: Relevance
“…Zinc demands also increase during pregnancy coincident with the rapid growth and differentiation of the embryo. Embryos in pregnant mice fed a ZnD diet beginning on d8 of pregnancy have a greatly increased risk of abnormal development (Dufner-Beattie et al, 2005. As noted previously (Dufner-Beattie et al, 2003b, Zip4 mRNA abundance was significantly increased in the maternal intestine and fetal VYS in mice fed the ZnD diet, while Zip5 and Zip1 mRNA abundance were unaltered (Figure 3).…”
Section: Zinc Reciprocally Regulates the Cellular Localization Of Zipsupporting
confidence: 61%
See 1 more Smart Citation
“…Zinc demands also increase during pregnancy coincident with the rapid growth and differentiation of the embryo. Embryos in pregnant mice fed a ZnD diet beginning on d8 of pregnancy have a greatly increased risk of abnormal development (Dufner-Beattie et al, 2005. As noted previously (Dufner-Beattie et al, 2003b, Zip4 mRNA abundance was significantly increased in the maternal intestine and fetal VYS in mice fed the ZnD diet, while Zip5 and Zip1 mRNA abundance were unaltered (Figure 3).…”
Section: Zinc Reciprocally Regulates the Cellular Localization Of Zipsupporting
confidence: 61%
“…In mammals, most of the ZIP proteins fall into one of two subfamilies, named subfamily II (3 members) and LIV-1 (9 members). Studies of knockout mice revealed that the members of subfamily II are particularly important when dietary zinc becomes limiting (Dufner-Beattie et al, 2005Peters et al, 2007). Less is known about the physiological functions of most LIV-1 family members.…”
Section: Introductionmentioning
confidence: 99%
“…Knockout mice with ZIP1 and/or ZIP3 deletions also have no apparent phenotype unless dietary zinc becomes limiting (Dufner-Beattie et al, 2005. Therefore, the effect of dietary zinc deficiency on Zip2-knockout mice was examined using several experimental protocols.…”
Section: Figmentioning
confidence: 99%
“…As a result, homozygous lm/lm pups suckling from lm/lm dams do not survive past the first 2weeks of neonatal development (Murgia et al, 2006). Mice with impaired ZIP1, ZIP2 or ZIP3 function display a decreased ability to absorb zinc from the diet, particularly during pregnancy when zinc absorption is normally increased (Dufner-Beattie et al, 2005;Dufner-Beattie et al, 2006). The ZnT8 knockout (KO) mouse model, which displays decreased insulin secretion, has provided insights into the endogenous function of ZnT8 as an importer of zinc into insulin-containing granules in pancreatic -cell islets (Hardy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%